Measurement of Family Strength - Euis Sunarti; Hidayat Syarief; Ratna Megawangi; Hardiansyah .; Asep Saefuddin; Husaini . (Media Gizi dan Keluarga, 2003)
Based on the family theory of structural functionalism, family is the first and the main porosity of human resource development. Family is the basic unit of society. The objectives of this study were to develop a measurement of family strength with high reliability and validity and to formulate policy implications to increase the family strength. 233 families from Leuwiliang district (19 villages) and Cibungbulang district (15 villages) were analyzed. Family strength data consisted of informations on physical resources, non-physical resources, family problems, copping mechanism, physical well-being, social welll-being, and psychological well-being. Applying Alpha Cronbach analysis, the family strength measurement had internal consistency coeficient of reliability 0.7 and applying factor analysis and Lisrel (Linear Structural Relationship) shared that there were there major latent variables of family strength, viz physical, social, and psychological. Strengthening the family should be an entegrated part of social economic, and family funcitioning development.